The Effectiveness of Classical Guidance Through Cinematherapy Techniques to Increase Self-Confidence of Students in Class VIII of SMP Negeri 1 Samarinda in the Academic Year 2024/2025 - Sasmito Jati , Ma'shum; Sari Pratiwi, Yasintha; Abdillah , Muhaimin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Abstract The purpose of this study was to determine the effectiveness of classical guidance through cinematherapy techniques on students' self-confidence. This type of research is quantitative by using experimental research method with the research design used is pre-experimental design with one group pretest-posttest design type. The instrument used in this study was a self-confidence scale with a Likert model. The population in this study were all 8th grade students of SMP Negeri 1 Samarinda. The sample used was 30 students with a sampling technique in the form of purposive sampling. The data analysis technique used was parametric statistics paired t test. Classical guidance services cinematherapy technique was carried out as many as 4 meetings. The results showed that the tcount value was greater than the ttable value, so it could be concluded that Ha was accepted and H0 was rejected. The pretest average score is 91.7 and the posttest average score is 113.5 so that classical guidance through cinematherapy techniques is effective for increasing student confidence. Classical guidance through cinematherapy technique can be one of the strategies to increase students' self-confidence.